Dynamic Elastic Modulus Variability in Anisotropic and Isotropic Materials: Comparison by Acoustic Emission - Cardim, Henrique Pina; Minillo, Larissa Queiroz; Nakao, Fernando; Ortenzi, Altibano (Journal of Research Updates in Polymer Science, 2023)
This study compared the variation of the dynamic elastic modulus (E) of three types of composite pipes made by the filament winding process and a steel alloy specimen, according to signal source changes. The specimens were produced with three different winding angles, i.e., ±50°, ±52.5°, and ±55°. The moduli were obtained through a known signal source and the angular variation, according to two sensors positioned over the specimen's surface. In a previous article, the variation in the velocity of acoustic emission (AE) signals, performed in the same type of pipes, was discussed based on the standards for glass fiber-reinforced epoxy (GFRE) filament wound specimens. This work took these preliminary findings to compare with the results found for steel alloy pipes (SAE 1020). This data was used with appropriate equations to determine the dynamic elastic moduli of each material. It was found that, even for small angular differences, the modulus changes position concerning the lamination angle. Thus, the lower the quality control, the lower the final product with composite materials. As expected, for isotropic materials such as steel alloys, the modulus remains constant along the angles, while for anisotropic ones, it is dependent on the principal directions of stress and strain, or on the other hand, dependent on the correlation between the angular wave velocity of the AE signals.